The time that money requires: Use of the future and critique of the present in financial valuation - Fabian Muniesa; Liliana Doganova (Finance and Society, 2020)
The future is persistently considered in the sociology of finance from two divergent, problematic angles. The first approach consists in supplementing financial reasoning with an acknowledgement of the expectations that are needed in order to cope with an uncertain future and justify the viability of investment decisions. The second approach, often labelled critical, sees on the contrary in the logic of finance a negation of the future and an exacerbation of the valuation of the present. This is an impasse the response to which resides, we suggest, in considering the language of future value, which is indeed inherent to a financial view on things, as a political technology. We develop this argument through an examination of significant episodes in the history of financial reasoning on future value. We explore a main philosophical implication which consists in suggesting that the medium of temporality, understood in the dominant sense of a temporal progression inside which projects and expectations unfold, is not a condition for but rather a consequence of the idea of financial valuation.
Keywords: 300; Finance; financial valuation; temporality; future; critique; philosophy